Sistem Informasi Inventaris Barang Berbasis WEB Pada Institut Teknologi Alberth Foenay Kupang - Merlin K. Talnoni; Mohamad Iqbal Ulumando; Risni Stefani (GLOBAL SCIENTS PUBLISHER, 2026)
Inventory management is a crucial aspect in supporting the smooth running of academic activities at universities. The Alberth Foenay Institute of Technology (ITAF) Kupang has a significant amount of assets, necessitating a structured, accurate, and easily accessible inventory system. This study aims to design and build a web-based inventory information system to improve the effectiveness and efficiency of campus inventory data management. The research method used is a qualitative method with observational data collection techniques, while the software development method applied is the Waterfall approach. The developed system provides data management features for goods, incoming goods, outgoing goods, warehouses, types of goods, units, and a dashboard as an information center. The results show that the web-based inventory system can facilitate faster, more accurate, and more integrated data collection, stock monitoring, and inventory reporting. With this system, inventory management at ITAF Kupang has become more organized, efficient, and easily accessible.